Boorman's pathology of the rat reference and atlas - Suttie, Andrew E.; Leininger, Joel R.; Bradley, Alys E. (Academic Press, an imprint of Elsevier, 2018)
Boorman’s Pathology of the Rat: Reference and Atlas, Second Edition, continues its history as the most comprehensive pathology reference on rat strains for researchers across science and medicine using rat models in the laboratory. It offers readers an added emphasis on the Sprague-Dawley and Wistar rat strains that is consistent with current research across academia, government, and industry. In addition, the book provides standard diagnostic criteria, basic content on histology, histological changes that result from drug toxicity and neoplasm, pathology terminology, and four-color photographs from the NTP archive and database. With updated references and photographs, as well as coverage of all rat strains, this book is not only the standard in the field, but also an invaluable resource for toxicologists, biologists, and other scientists engaged in regulatory toxicology who must make the transition from pathology results to the promulgation of meaningful regulations.--Provided by publisher.